The analysis of parental attitude towards active immunoprophylaxis and its influence on the implementation of an Immunization Schedule among children in Poland. Issue 3 (3rd July 2018) - Olszewska, Marta; Smykla, Barbara; Gdańska, Marta; Kiełbasa, Grzegorz; Ficinski, Matthew; Szymońska, Izabela; Starzec, Katarzyna; Kwinta, Przemko
ABSTRACT: The analyses of parental attitude towards active immunoprophylaxis and its influence on the implementation of an Immunization Schedule (IS) among children under 2 years of age in Poland were performed. Three-hundred legal guardians filled out a questionnaire, and 83.67% of parents admitted having concerns about vaccinations in their children. Most respondents reported a previous contact with anti-vaccination statements (AVS). The predisposing factors for such contacts included a more advanced parental age, higher education, good financial status, and living in a city of over 100, 000 inhabitants. A delay in age-appropriate immunization was found in 40.49% of children. Findings suggest that the problem of vaccine hesitancy is common. Dissemination of clear and homogenous information campaigns as a response to AVS may increase vaccine acceptance among parents.